Violation of the Professional Code of Ethics for Judges and its Consequences for Judicial Administration - Maisyur Arif (Pancasila and Law Review, 2021)
The phenomenon of violation of the judge's code of ethics in the practice of the judiciary is a serious problem. The purpose of this research is to find out if there is a violation of the professional code of ethics of the judge, and its impact on the administration of justice. The method used in this writing is normative juridical. The result of the discussion in this paper is that violations of the professional code of ethics owned by judges have led to practices of collusion, corruption and nepotism. All of these things are caused because there are gaps for actors to make offers, provide opportunities and weak supervision. The suggestion given by the author is that there are efforts to improve the judge's internal self and external improvements, namely in the form of increased supervision of judges through the judicial commission.